Sexual activity of Subcarpathia residents - Kremska, Anna; Wróbel, Romana; Pieniążek, Anna; Cecuła, Monika; Żurawska, Justyna; Kołodziej, Bernadeta (European Journal of Clinical and Experimental Medicine, 2017)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction. Sexuality is an inseparable attribute of humans that makes it possible to take new challenges connected with it at every stage of life and to enjoy its new aspects as well as to accept the resulting restrictions. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Aim. The objective of this study was to compare how sexual activity changes in different age groups. An important step in achieving the main objective was to determine the age of sexual initiation, the number of sexual partners and the most commonly used methods of preventing pregnancy. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. The study was conducted between 2010 and 2013 among 924 persons. The respondents were the students of secondary schools, technical schools, post-secondary schools and the University of Rzeszów. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. Two-thirds of a group aged 16-18 did not start sexual relations. Only 2% of the respondents at the age groups of 16- 18,19-23 and only 1% of the respondents at the age group of 24-48 began having sexual relations under the age of 15. 67% of adolescents from big cities began sexual relations. 33% of the secondary schools/technical schools respondents, 51% of the post-secondary schools respondents, 35% of a higher education institution respondents most commonly use condoms as a method of contraception. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. The average age of sexual initiation is gradually decreasing in each age group. Most respondents declare having one sexual partner. The respondents from big cities more often begin sexual relations. Condoms are the most commonly used method of contraception among the respodents in all age groups.